2014
DOI: 10.1104/pp.114.238238
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Cyclic Electron Flow around Photosystem I to Changes in Photorespiration and Nitrate Assimilation

Abstract: Photosynthesis captures light energy to produce ATP and NADPH. These molecules are consumed in the conversion of CO 2 to sugar, photorespiration, and NO 3 2 assimilation. The production and consumption of ATP and NADPH must be balanced to prevent photoinhibition or photodamage. This balancing may occur via cyclic electron flow around photosystem I (CEF), which increases ATP/NADPH production during photosynthetic electron transport; however, it is not clear under what conditions CEF changes with ATP/NADPH deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 62 publications
5
89
0
Order By: Relevance
“…This model prediction is consistent with experimental findings that CEF is only important under high light levels (Munekage et al, 2008;Walker et al, 2014). In a CEF mutant of Chlamydomonas reinhardtii, the deficiency in CEF could be compensated by the combined effect of the mitochondrial ETC and WWC (Dang et al, 2014).…”
supporting
confidence: 79%
“…This model prediction is consistent with experimental findings that CEF is only important under high light levels (Munekage et al, 2008;Walker et al, 2014). In a CEF mutant of Chlamydomonas reinhardtii, the deficiency in CEF could be compensated by the combined effect of the mitochondrial ETC and WWC (Dang et al, 2014).…”
supporting
confidence: 79%
“…Studies have suggested that nitrate reduction in the cytosol is limited by reductant availability and that photorespiration provides reductant for nitrate assimilation by shuttling malate through the cytosol (32,34). Similarly, nitrate reduction could serve to consume excess electrons when the ATP:NADPH demand from the primary metabolism is higher than what is produced from the light reactions of photosynthesis (82). Such energy balancing between supply and demand is important to prevent photoinhibition of the light reactions, although other means of balancing the ATP/NADPH production ratio, such as photosystem I cyclic electron transport and the water-water cycle, are well established (41,59,87).…”
Section: Photorespiration and Nitrate Assimilationmentioning
confidence: 99%
“…The results of using an HPR of 12 was, as expected from previous studies (Yin et al, 2006;Walker et al, 2014), a decrease in the fraction of alternative electron transport, yielding a negligible cyclic electron flux around PSI and a low fraction of electrons allocated to alternative electron sinks. However, the model also predicted an increase in the flux of electrons consumed by the Calvin cycle.…”
Section: + ( /Atp Stoichiometry Of Atp Synthasesupporting
confidence: 65%
“…Screening of mutant collections allowed the identification of NPQ mutants (Niyogi et al, 1998;Li et al, 2000b), whereas manipulations in gene expression (Niyogi et al, 2005) There are also strong limitations to the experimental study of cyclic electron transport and alternative electron sinks. Although several techniques are available for targeting different mechanisms Munekage et al, 2002;Driever and Baker, 2011;Walker et al, 2014;Strand et al, 2016a), these techniques do not provide a complete quantification of the different fluxes of electrons and their regulation in response to environmental conditions and rely on assumptions that are difficult to verify experimentally (Driever and Baker, 2011;Johnson, 2011;Walker et al, 2014;Fan et al, 2016).…”
Section: Cyclic Electron Transport Around Photosystem I (Psi) Includimentioning
confidence: 99%